2012
DOI: 10.1177/1087054712454571
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among ADHD, Self-Esteem, and Test Anxiety in Young Adults

Abstract: The findings of this study suggest that TA, well known to affect success on tests, is correlated with ADHD. Therefore, interventions for ADHD should include components aimed at reducing TA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 63 publications
(69 reference statements)
4
39
0
Order By: Relevance
“…It is also interesting to note that the highest raw impairment in both groups was in self-concept. To a degree, this fits with the typical developmental challenges of the late adolescent and emerging adult periods, which in particular are marked by struggles with self-identity and pressure to establish independence in the “grown-up” world (Arnett, 2004), yet the large difference noted between ADHD and non-ADHD also reflects the state of the literature that suggests those with ADHD—even those in the “high-functioning” college student population—characteristically have a more negative self-view than other peers (Canu & Carlson, 2007; Dan & Raz, 2015; Shaw-Zirt, Popali-Lehane, Chaplin, & Bergman, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to note that the highest raw impairment in both groups was in self-concept. To a degree, this fits with the typical developmental challenges of the late adolescent and emerging adult periods, which in particular are marked by struggles with self-identity and pressure to establish independence in the “grown-up” world (Arnett, 2004), yet the large difference noted between ADHD and non-ADHD also reflects the state of the literature that suggests those with ADHD—even those in the “high-functioning” college student population—characteristically have a more negative self-view than other peers (Canu & Carlson, 2007; Dan & Raz, 2015; Shaw-Zirt, Popali-Lehane, Chaplin, & Bergman, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Dan and Raz (26), reported that test anxiety well known to affect success on tests, is correlated with ADHD. Therefore, interventions for ADHD should include components aimed at reducing test anxiety (26). Among the studies evaluating the text anxiety, we have not come across with a research directly gravitated towards ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Children with ADHD report lower self-esteem and show an increased rate of academic failure and test anxiety. Cognitive problems such as impaired working memory and reduced executive function are also common (Dan and Raz, 2012). Adolescents with ADHD struggle with delinquency, substance abuse and numerous comorbid psychiatric disorders such as oppositional defiant disorder, conduct disorder, mood disorders, anxiety disorders, and learning disorders (Biederman, 2005).…”
Section: Evidence From Human Studies Suggest That Maternal Metabomentioning
confidence: 99%